Wanita Menurut Pandangan Filsafat Jawa - Mudjajadi Mudjajadi (Jurnal Filsafat "WISDOM", 1999)
The study was carried out with the reasons that most of the empirical studies on women, including the Javanese women, paid very little attention or, let's say completely ignored the philosophical view that plays behind the fate of women. Through many historical studies it has proved that Javanese philosophy does really exist. The Javanese philosophy even contains some clear guidance on how a Javanese women should select a number of hopeful female models which can be presented openly, and which are futher related with the view of existence unit which is mystical religious in nature. In this sense a Javanese women however high her status may be should always be aware of her proper place in the family, so that, however highly educated she man be, she should always be able not disgrace the status of her husband and her family. Besides, as potrayed in the two figures. Dewi Sumbadra and Srikandi, a Javanese women does not place herself in a too subordinate position